Zdobyć awangardę [rec. Aleksander Wójtowicz: Nowa Sztuka. Początki (i końce). Kraków: Wydawnictwo Uniwersytetu Jagiellońskiego, 2017, ss. 280.] - Baron-Milian, Marta (Śląskie Studia Polonistyczne, 2017)
The text discusses the most important theses of Aleksander Wójtowicz’s study devoted to the circles of New Art and it subjects them to critical reading. The author focuses primarily on confrontation of various narrative lines, which we encounter outside the mainstream research on the interwar avant-garde. What seems especially interesting is how Wójtowicz captures the history of the literary experiment as a space of oppression and exclusion, and above all, the struggle for discursive domination, in which gradually New Art was superseded by the avant-garde.